Organizing Non-formal Education Activities for Out-of-School Children - Pathumcharoenwattana, Worarat; Pathumcharoenwattana, Wirathep; Charungkaittikul, Suwithida; Chuymanee, Kotchaworn; Chudasring, Ravee (Hatyai Academic Journal, 2023)
Out-of-school children are children who do not have access to the education system and are not entitled to an education. These children include children with disabilities, children and youth in the justice system, stateless children, children of migrant workers, children in poor communities, ethnic minority children, and the children of Muslim immigrant parents across the country and in the southernmost border area. Educational activities for these children should involve non-formal educational activities that are likely to be flexible and consistent with their characteristics and needs, such as basic knowledge, life skills development, and career skill development. The process of organizing activities should start with studying the nature and characteristics of the children, analyzing their needs and basic interests, organizing, and monitoring as well as assessing the activities